Design and Performance Evaluation of Vegetable Shredder - Suriwong, Voraluck; Inrirai, Patcharaporn; Swaeng-ngam, Surintraporn; Sumrit, Thawanrat; Khamphumee , Thipyarat; Meebun, Sarayut (Burapha Science Journal, 2024)
Background and Objectives :Vegetable shredders were generally designed to be used to reduce the size of agricultural products. The design and development of vegetable shredder to get a beautiful shapes and quality suitable for further process in healthy products is still lacking knowledge. Therefore, this research was aimed to design and build a vegetable shredder and study the effect of rotational speed on the efficiency of the shredder. Methodology : Study and calculate the important values for the main component of vegetable shredder. Then, five types of vegetables used to test the shredder performance were potato, carrot, radish, cucumber and onion with the rotational speeds of the inverter included 500, 600, 700 and 800 rpm. The loss percentage, the percentage passing the required quality criteria and the production capacity of vegetable shredder were determined. Main Results : The vegetable shredder has the following main components: machine structure, blade plate, blade plate cover, raw material input slot, 0.5 hp electric motor and inverter (rotational speed device). The result showed that the loss percentage from the shredder’s operation under various conditions was 5.28%±0.84 - 19.15%±1.89, and the different types of vegetables used different rotational speeds. The suitable rotational speed with a high percentage passing the required quality criteria in potato, carrot and onion was at 700 rpm, while the rotational speed at 600 and 800 rpm were suitable with radish and cucumber, respectively. In addition, the vegetable shredder had a significantly higher production capacity than the manpower to cut vegetables (p<0.05). Conclusions : To save production costs and get high-quality products or high percentage pass the required quality criteria, the vegetable shredder designed and built in this research was suitable for chopping vegetables with good shapes and homogeneous textures, such as potatoes, carrots and radishes.